Оцінка основних похибок вимірювання показника заломлення аналіту приладом на основі явища поверхневого плазмонного резонансу - Дорожинський, Гліб Вячеславович (НТУ "ХПІ", 2015)
Встановлено, що основними джерелами похибок вимірювання показника заломлення приладом на основі поверхневого плазмонного резонансу є температурний режим його роботи, довжина хвилі лазеру та топологія поверхні чутливого елементу. Основними напрямками зменшення величин похибок вимірювання є збільшення довжини хвилі лазеру, зменшення шорсткості поверхні чутливого елементу та стабілізація температурних режимів роботи приладу. Результати досліджень можуть бути використані для вдосконалення існуючих та створення нових приладів на основі поверхневого плазмонного резонансу.

The main sources of measurement errors of the refractive index of the analyte for the device based on the phenomenon of surface plasmon resonance "Plasmon-6" were identified: laser diode wavelength, temperature control operation, surface topology of sensing element metal film. Based on numerical analysis, it was determined that the largest contribution to the measurement error of the refractive index of the analyte component makes temperature error δNT= 54,24 • 10⁻⁵, and the least - the surface roughness of the metal layer sensitive element δNS = 8·10⁻⁵. The error of approximation for the laser wavelength of 650 nm is δNA = 21·10⁻⁵. It defines the main directions of the major decrease measurement errors are: increasing wavelength excitation of surface plasmon resonance, reducing the surface roughness of the metal layer of the sensing element and stabilization of temperature modes of the device. The practical significance is that the results of numerical analysis can be used to improve existing and create new devices based on surface plasmon resonance.
Evaluation of basic errors of measurement of the refractive index of the analyte device based on the phenomenon of surface plasmon resonance
Keywords: довжина хвилі випромінювання; шорсткість поверхні; температура; ППР; surface roughness; temperature